Ageing Issues Among the Pashtun Folk in Quetta City of Balochistan - Rahim, Dr Muhammad; zafar, Dr Huma; Nasir, Muhammad (Journal of Quranic and Social Studies, 2023)
Aging is an integral part of each society in the world. The advancement of medicine and technology has increased life expectancy to a determined level, which has resultantly raised the elderly population. Pakistan and generally Balochistan are also in this queue, but unfortunately, the government has not framed such policies to accommodate and secure the elderly people from the hardships of life and make them independent. This study highlights the issues of elderly people in Quetta City, where the elders are mostly illiterate and hardly adjustable in technological settings. The study was carried out through a sequential technique of non-probability sampling, where data was collected from 28 informants through an unstructured interview guide to the saturation level. The findings depict that the old cohort has several issues in the research locale. These issues are social, familial, economic, psychological, mental, emotional, healthcare, and likewise. The study suggests that the government should consider the weak segment of society and farm strategies to safeguard the rights and the fundamental life of the aging population.